Analisis Resiko Kredit Pada PT. Bank Sumut Cabang Pembantu Tanjung Pura - Edi Saputra Matondang (Jurnal Riset AKuntansi dan Bisnis, 2020)
This study aims to analyze the credit risk ratio to determine whether the bank is in the unhealthy category according to Bank Indonesia. In addition, by analyzing credit risk, it can be seen that the company's financial performance from year to year. This research uses descriptive quantitative research with the data used are financial reports. To obtain the data needed in this study, the authors used data collection techniques. Methods by means of documentation, calculating research variables, analyzing research variables and making conclusions. The results of this study indicate that: the Bank's financial credit risk seen from the NPL factor of PT Bank Sumut Capem Tanjung Pura is included in the category of a healthy bank because the level of NPL that grows is still below the stipulated Bank Indonesia Standard, which is below 5%. Credit risk seen from the LDR at PT Bank Sumut Tanjung Pura Sub-Branch is in the bad or unhealthy category because the LDR level is still above the standard set by Bank Indonesia, which is ?78% -94%.